Comparing the Effectiveness of Bacterial Nanocellulose Dressing and Silver Sulphadiazine in Mid Dermal Burn Wound: A Systematic Review - Nyoman Ananta Awatara, Ida Bagus; Zarasade, Lobredia; Hariani, Lynda (Journal of Neonatal Surgery, 2025)
Burns are damage to the skin that were caused by heat or cold trauma (frost bite). This damage can include tissue under the skin and can also cause systemic problems that will require a very long treatment time. Silver Sulfadiazine (SSD) is the most common topical antimicrobial treatment for burns. Silver Sulphadiazine has been found to have a cytotoxic effect on fibroblast cells, thereby affecting the wound healing process. Bacterial nanocellulose dressing is a new type of dressing that is currently performing and researched. Bacterial nanocellulose dressings properties are suitable for wound healing, but they lack antibacterial properties. This quantitative Systematic Review design aims to study the effectiveness of Bacterial Nanocellulose Dressing compared to Silver Sulfadiazine in patients with mid dermal burns. The variable studied was the rate of epithelialization. Studies were selected from various databases within the last 20 years. After selecting studies that meet the inclusion criteria, exclusion criteria and assessing the quality of the literature, the selected studies will be processed. Study selection using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, from the database search obtained 7 articles on the Pubmed database and 5 articles on the Cochrane database. Then the studies were excluded again based on the title and abstract so that 2 studies remained and were analyzed in this study. Both studies were randomized controlled clinical trials, and a total of 100 samples were obtained. The samples were split into two groups, Silver Sulfadiazine control group and Bacterial Nanocellulose Dressing intervention group. From the results of the study, it was described that there was a difference between the epitalization rate in the SSD group and the bacterial nanocellulose group. The study by Aboelnaga et al., 2018, stated that by multivariable regression analysis, the mean epithelialization rate of the nanocellulose group was 4.3 days faster than the SSD group, without any significant difference. And a study by Piatkowski et al., 2011, said that the healing time in both treatment groups was similar. From the findings, it can be concluded that Bacterial Nanocellulose Dressing has the ability to accelerate the rate of epithelialization in burn wounds compared to SSD. Apart from the rate of epithelialization, Bacterial Nanocellulose Dressing is better in terms of pain and more cost effective than SSD.